(untitled) (Medicine Today, 2024)
Introduction: Posterior lumbar interbody fusion (PLIF) is a reliable treatment option for patients with Lumbar canal stenosis & spondylolisthesis; providing spinal stabilization in a balanced alignment with the disc space height restored and with the neural elements being decompressed mechanically. The titanium cages provided immediate stability to spinal levels, restoration of the disc space and neuro-foraminal area, and an increased surface area leading to successful fusion. Materials and Methods: This prospective study was carried out at the Department of Orthopedic Surgery at DMCH, Dhaka within the defined period. All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using Statistical Package for Social Science. The results were expressed as percentage and mean ± SD and p<0.05 was considered as the level of significant. Result: Mean age of the study population was 51.32±8.29 with a female: male ratio 1.6 :1 where maximum patient was housewife (57.14%). 60.72% patients had only single level involvement while 39.28% patients had multi-level involvement. Mean VAS score reduced significantly at final follow-up (6.55±0.66 to 2.29±0.46 for back pain and 6.59±0.65 to 1.21±0.42 for leg pain. Mean ODI score decreased significantly from 56.71±3.09 to 15.82±3.46 at final follow-up. Radiologically Grade-I fusion achieved in 89.28% cases. Overall functional outcome was excellent (89.29%) & good (7.14%) according to Modified Macnab criteria. Conclusion: Posterior lumbar interbody fusion (PLIF) with cage and bone graft in the treatment of degenerative lumbar spinal canal stenosis provides excellent neurological and functional outcome and fusion rate at final follow-up. Medicine Today 2024, Vol.36 (2): 72-75